Racial/Ethnic Differences in Predictors of Mental Health Treatment in Persons with Comorbid Diabetes and Depression. Issue 6 (18th September 2016) - Hawkins, Jaclynn; Watkins, Daphne C.; Bonner, Timethia; Thompson, Terry L.
Abstract : Diabetes and depression are two of the most frequently diagnosed health conditions in the United States and often co-occur. The present study examines racial/ethnic differences in predictors of mental health service use among a national sample of African Americans, Hispanics, and non-Hispanic Whites with a self-reported diabetes and depression diagnosis. Multiple logistic regression was used to analyze a cross-sectional sample ( N  = 3377) of the 2012 National Health Interview Survey (NHIS), a nationally representative, cross-sectional survey. African Americans were less likely to have visited a mental health professional in the last 12 months (odds ratio [OR] = .634, confidence interval [CI] [0.429, 0.911]). Significant odds ratios also uncovered results for the "never married" (OR = 1.737, CI [1.322, 2.281]) category. Also for the entire sample, being 55 years or older (OR = .352, CI [0.234, 0.533]) was found to be strongly associated with mental health service use for individuals with diabetes. Being unemployed or not in the labor force increased the odds of mental health service use in persons with diabetes and depression, whereas having less than a high school diploma or Graduate Equivalency Diploma decreased odds of visits (OR = .611, CI [0.394, 0.945]) as did not having health insurance (OR = .540, CI [0.365, 0.800]). Racial/ethnic variation in mental health service utilization exists among persons with self-reported diabetes and depression. Due to the challenges associated with comorbid depression and diabetes, as well as the impact depression can have on diabetes self-management, it is imperative that more strategies for managing both depression and diabetes be explored.